Seroprevalence of markers of transfusion transmissible infections among blood donors at a tertiary care hospital blood bank: a 5 year retrospective study - Yasmeen, Irm; Kour, Supinder; Khurshid, Imran; Malik, Aasifa (International Journal of Research in Medical Sciences, 2019)
Background: Transfusion transmitted infections (TTIs) can be caused by various microorganisms present in the blood of apparently healthy donors. The recipient may get infected after being transfused with the unsafe blood. It is mandatory to screen the blood for HIV 1 and 2, HBV, HCV, Syphilis and Malaria. This study was undertaken to investigate the seroprevalance of Transfusion transmitted infections among blood donors at our tertiary care centre and to compare our study with other studies conducted at different hospitals of the country as well as outside. Methods: A retrospective review of blood donor records was made over a period of 5 years with effect from January 2014 to December 2018 at blood bank, department of Blood Transfusion and Immunohaematology, SKIMS, Soura, Srinagar. Both voluntary and replacement blood donors were selected after taking proper history and examination were included in the study. Serum samples were screened for HIV 1 & 2, HBV (HBsAg) and HCV using ELISA with 3rd generation kits. Results: A total of 56325 blood donors were screened. Out of total 55346 (98.2%) were males and 979 (1.73%) were females. Among them 38969 (69.1%) were replacement donors and 17356 (30.8%) were voluntary donors. The seroprevalance of HBV (HBsAg), HCV and HIV 1and 2 was 0.24%, 0.17% and 0.01% respectively and overall seroprevalance of TTIs was 0.43%. Conclusions: Continuous improvement and implementation of newer techniques like NAT and chemilumenescence for testing of blood for TTIs will reduce the risk of acquiring these infections. lance